A percepção do vivido de psicólogos que atuam no consultório na rua em São Luís - MA - SANTOS, Ramon Damião De Sena (2024)
This research aimed to explore the lived experience of psychology professionals working at the Consultório na Rua (Street Clinic) in São Luís, Maranhão, Brazil. Given the plural and growing nature of this reality, which calls for humanized healthcare closer to the needs of the population, this study delves into the topic from its situational, mutable, and non-crystallized condition to the data presented on the reality of São Luís based on the service records in the e-SUS system and an interview with a psychology professional. This qualitative descriptive study employed Amedeo Giorgi's empirical phenomenological method for data analysis. The findings indicate that while the challenges faced by street psychologists mirror those identified in previous literature reviews, there are unique aspects to this particular context. These challenges have been observed over the years in various forms of care, even during the pandemic, which posed unprecedented challenges worldwide, including for street clinic operations. The participant's account highlights the importance of learning, constant openness to the new, and embracing the emerging aspects of this context, as well as the efforts to ensure that the work is widely recognized by health services, ultimately reducing the various forms of neglect and violence experienced by individuals in healthcare units. Additionally, the results pave the way for further research in this area, given the limitations of existing studies on this lived reality.